ChemInform Abstract: Efficient Protocol for Synthesis of Pyrazolo[3, 4‐a]acridines. Issue 5 (January 2016) - Satheeshkumar, Rajendran; Kaminsky, Werner; Sparkes, Hazel A.; Rajendra Prasad, Karnam Jayarampillai
Abstract: Six title compounds of type (VI) are prepared by a three‐step reaction sequence.